Traumatic Urethral Injury without Pelvic Fracture in an Adult Female. (2010) - Bockholt, Nathan A.; Nepple, Kenneth G.; Powell, Charles R.; Kreder, Karl J.
Abstract : A 23-year-old female was involved in a motor vehicle collision with multiple injuries, including a right acetabular fracture, but no pelvic fracture. Urology consultation was obtained due to difficulty placing a urethral catheter. Examination revealed a longitudinal urethral tear with vaginal laceration extending 2 cm from the urethral meatus proximally toward the bladder neck. The longitudinal urethral tear was repaired primarily. Traumatic female urethral injury in the absence of a pelvic fracture is an exceedingly rare occurrence.